Generation Z and CSR: antecedents of purchasing intention of university students - Arıker, Çağla; Toksoy, Andaç (Kafkas University, 2017)
Objective of this research is to examine hierarchy between three factors that affect purchasing intention of Generation Z for products of companies implementing CSR projects. Since Generation Z will become target market of many companies in the shortrun, studies regarding their purchasing intention, sign of actual purchase, are valuable. Three independent factors include “Perception of Primary Motives”, “General Attitudes”, and “Preconditions to Prefer”. Data was collected through a survey with scales measuring research variables. Four Regression Models were tested to see hierarchical effect of independent variables. The results showed that positive perceptions and attitudes alone aren‟t sufficient to create strong purchasing intention for CSR related products. Determination coefficcient increased as “Preconditions to Prefer”, namely affordable price and good quality products, were entered into the model, respectively. Managers targeting Generation Z are suggested to implement CSR projects but not at the expense of affordable price and expected quality standards.

Bu araştırmanın amacı, Z jenerasyonunun, kurumsal sosyal sorumluluk projeleri (KSS) uygulayan şirketlerin ürünlerine yönelik satın alma eğilimini etkileyen üç faktörün arasındaki hiyerarşiyi incelemektir. Z jenerasyonu yakın gelecekte pek çok şirketin hedef pazarını oluşturacağından, satın alma eğilimlerine yönelik araştırmalar değerlidir. Üç bağımsız değişken “Algılanan Birincil Güdüler”, “Genel Tutumlar” ve “Tercihin Önşartları”dır. Veriler araştırma değişkenlerini ölçmeye yönelik ölçekleri içeren bir anket kullanılarak toplanmıştır. Bağımsız değişkenlerin “Satın Alma Eğilimi” üzerindeki hiyerarşik etkisini görmek için dört adet Regresyon Modeli test edilmiştir. Sonuçlar, olumlu algılamaların ve tutumların KSS uygulayan şirketlerin ürünlerine yönelik güçlü satın alma eğilimi yaratmakta tek başına yeterli olmadığını göstermiştir. Belirlilik katsayısı, “Tercihin Önşartları” arasında bulunan “Ulaşılabilir Fiyat” ve “İyi Kalitede Ürünler” değişkenleri modellere eklendikçe yükselmiştir. Bu nedenle, hedef pazarları arasında Z jenerasyonu bulunan yöneticilere, KSS projelerini uygularken, ulaşılabilir fiyat ve beklenen kalite standartları konularındaki önşartları sağlamaya devam etmeleri önerilir
GENERATION Z AND CSR: ANTECEDENTS OF PURCHASING INTENTION OF UNIVERSITY STUDENTS
Keywords: Generation Z; CSR; Preconditions To Prefer; Z Jenerasyonu; KSS; Tercihin Önşartları